DESIGN OF E-TOURISM APPLICATION AS TOURISM PROMOTION TOURISM REGENCY OF TANGGAMUS - Sri Hartati; Mar’atus Sholehah; Afrizal Martin (STMIK Pringsewu Lampung, 2017)
Tourism world not was something new for everyone. Tourism has become industrial who in every tourist destinations. Of various facilities and ease and also entertainment provided to support various activity tourism has been provided by the government or the supporting component tourism other. One of the facilities that may be developed is e-tourism. E-tourism can inform us tourist destinations with various the needs and supporting facilities for users especially tourists .Services rendered website as a form of incentives could be done by the visitors. As well as design system of flow of data on the application was used in the Data Flow Diagram (DFD) and to design of the tables on a database using Entity Relationship Diagram (ERD). After design systems and a database , the next stage is transform Implementation design. To where the implementation of this system uses a programming language PHP and MySQL. With the existence of this application can ease the community to found any information on objects Tanggamus and to be able to share new information possessed to others with the website.